2003
DOI: 10.1046/j.1365-246x.2003.01884.x
|View full text |Cite
|
Sign up to set email alerts
|

Micro and macroscopic models of rock fracture

Abstract: SUMMARY The anelastic deformation of solids is often treated using continuum damage mechanics. An alternative approach to the brittle failure of a solid is provided by the discrete fibre‐bundle model. Here we show that the continuum damage model can give exactly the same solution for material failure as the fibre‐bundle model. We compare both models with laboratory experiments on the time‐dependent failure of chipboard and fibreglass. The power‐law scaling obtained in both models and in the experiments is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
152
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(161 citation statements)
references
References 57 publications
5
152
0
4
Order By: Relevance
“…For creep-relaxation experiments on rock, Hao et al (2014) found that the exponent β is about 2/3 (α = 2.5). Finally, in the analysis of viscoelastic fiber bundle models (Kun et al, 2003;Turcotte et al, 2003;Hao et al, 2012) β = 0.5 (α = 3). It should also be noted that, whereas Voight (1988Voight ( , 1989 originally proposed that precursory signals follow a single trend, an alternative view is that the trend evolves with time from conditions for α ≈ 1 to conditions for α ≈ 2 (Kilburn and Voight, 1998;Kilburn and Petley, 2003;Kilburn, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For creep-relaxation experiments on rock, Hao et al (2014) found that the exponent β is about 2/3 (α = 2.5). Finally, in the analysis of viscoelastic fiber bundle models (Kun et al, 2003;Turcotte et al, 2003;Hao et al, 2012) β = 0.5 (α = 3). It should also be noted that, whereas Voight (1988Voight ( , 1989 originally proposed that precursory signals follow a single trend, an alternative view is that the trend evolves with time from conditions for α ≈ 1 to conditions for α ≈ 2 (Kilburn and Voight, 1998;Kilburn and Petley, 2003;Kilburn, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…4, was previously analyzed by Lyakhovsky et al (1997a) to describe a stickslip motion under a constant rate of applied deformation. The solution of equations (5, 6) without irreversible strain accumulation prior to the final brittle failure gives a power-law time-to-failure relation consistent with the power-law seismic activation prior to some large earthquakes (Ben-Zion and Lyakhovsky, 2002;Turcotte et al, 2003). The analytical power-law scaling was obtained for a constant applied stress that mimics natural boundary conditions for a system at the stage of accelerating seismic release.…”
Section: Decay Of Activity (Analytical Solution)mentioning
confidence: 58%
“…Rabotnov (1988) related the damage variable to a reduction of the effective cross-section area that supports the load. Fiber-bundle models of damage (Newman & Phoenix, 2001;Turcotte et al, 2003) share the same idea, where cracks are equivalent to torn fibers.…”
Section: Theorymentioning
confidence: 99%
“…In order to suppress possible voltage spikes, acquired AE signals with duration < 3 µs and count number < 3 were filtered out. Spatial identification of the arch's damaged zones was performed by applying triangulation equations to the received AE signals in order to localize the AE sources as active and propagating crack tips (Shah and Li, 1994;Shiotani et al, 1994;Grosse et al, 1997;Guarino et al, 1998;Ohtsu et al, 1998;Colombo et al 2003;Turcotte et al, 2003;Aggelis et al, 2013).…”
Section: Resultsmentioning
confidence: 99%